NEW POSSIBILITIES FOR MONITORING METHOTREXATE EFFICACY IN RHEUMATOID ARTHRITIS - Yu. V. Muravyev (Научно-практическая ревматология, 2015)
The review deals with the prediction of the therapeutic effect of methotrexate in rheumatoid arthritis, by determining its level in the red blood cells.